2016
DOI: 10.1111/ajco.12569
|View full text |Cite
|
Sign up to set email alerts
|

Determining the cost‐effectiveness of endoscopic surveillance for gastric cancer in patients with precancerous lesions

Abstract: Endoscopic surveillance of gastric premalignancies can be a cost-effective strategy for GC prevention. Its implementation requires careful assessment on factors influencing the actual cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
0
15
0
3
Order By: Relevance
“…Using an adapted WTP threshold of $44,000/QALY, they reported that the one-time screening with select annual surveillance was cost-effective (ICER: $34,000/QALY) while biennial screening was not cost-effective (ICER: $525,900/QALY). 48 Table 3 details additional model comparisons of various base case age and sex combinations, all of which consistently demonstrated that screening with annual surveillance if indicated generated lower ICERs compared with the biennial strategy. Subgroup analysis, however, demonstrated that cost-effectiveness was heterogenous across combinations of age group and sex.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…Using an adapted WTP threshold of $44,000/QALY, they reported that the one-time screening with select annual surveillance was cost-effective (ICER: $34,000/QALY) while biennial screening was not cost-effective (ICER: $525,900/QALY). 48 Table 3 details additional model comparisons of various base case age and sex combinations, all of which consistently demonstrated that screening with annual surveillance if indicated generated lower ICERs compared with the biennial strategy. Subgroup analysis, however, demonstrated that cost-effectiveness was heterogenous across combinations of age group and sex.…”
Section: Resultsmentioning
confidence: 83%
“…A total of 17 articles were ultimately included for qualitative analysis; 8 studies were decision analyses of endoscopic screening for GC, 33 40 4 were decision analyses of endoscopic surveillance of gastric preneoplasia, 41 44 and 5 were decision analyses of both screening and surveillance. 45 49 Whereas 6 studies were from high-incidence countries, 34 , 35 , 37 40 11 were from low–intermediate incidence countries 33 , 36 , 41 49 as defined by IARC. Details of each of these studies are provided in Tables 1 – 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations